Customer Value in Retirement Service Offerings : An Explanatory Study of Perceived Customer Value in Choice of Retirement Service Offerings - Lim, Shing Loo (2016)
The issue of an individual's post-retirement economic sustainability is cause for concern given the current demographic trends and economic environment factors. In Malaysia, statistics highlight the inadequancy of retirement funds offered through the formalized EPF retirement scheme (EPF Annual Report, 2014). Thus, individuals have to seek alternative retirement service offerings as means to boost their retirement funds. In light of the retirement service offerings' variety available and complexity of the decision-making process, this research sets out to explore customer value in retirement service offerings. Data was collected through semi-structured interviews from 30 respondents across demographic profiles. The results reveal that customers mainly perceive value in the dimensions of product, company and service/employee, which subsequently drives their choice of retirement service offerings. The core differentiation that determines the satisfaction of customers were due to service agents whom were able to deliver beyond the expected service quality. The existence of customer-adviser relationships, which brings about confidence and comfort were aspects of perceived customer value which results in customer satisfaction. On the contrary, opportunistic behaviour among agents, as a result from the inherent industry compensation structure drove negatively perceived value. Emergent themes were found in areas where individuals try to mitigate uncertainty through tangible assumptions of their investments. Furthermore, illuminating perspectives were derived in how ethnicity influences the way individuals accumulate assets through different instruments. Implications of this research presents opportunities from managerial and regulatory perspectives. It is pertinent for financial service providers to approach customer-value based segmentation in a holistic manner, given the interdependencies of one customer value dimension to the other. Furthermore, opportunities to create more sustainable retirement systems require policymakers' commitment in areas of financial inclusion, education and awareness as well as transparent management of the agencies involved.